CRANIOMETRIC VARIATION AND SUBSPECIFIC DIFFERENTIATION IN THRICHOMYS APEREOIDES IN NORTHEASTERN BRAZIL (RODENTIA, ECHIMYIDAE) - Bandouk, A. C. [UNESP]; Dosreis, S. F. (Gustav Fischer Verlag Jena, 1995)
Thrichomys apereoides is an echimyid rodent which ranges in distribution from northeastern and central Brazil into Paraguay. Five subspecies are recognized, although each form is not well characterized and diagnosis is based primarily in pelage color variation. In this study we employed procedures from multivariate statistics to assess the systematic status of subspecies described from northeastern Brazil. The results of the craniometric analysis cannot be reconciled with the subspecies currently recognized for northeastern Brazil. Populations assigned to T. a. laurentius and T. a. inermis form a continuum of variation in cranial size, although they differ in cranial shape from a population from the locality of Bodoco in the state of Pernambuco. The implications of these findings for the systematics of T. apereoides are discussed.